Association between family functioning and academic burnout among vocational college nursing students: mediating role of academic self-efficacy - Yanying Yang; Sujiao Liu; Min Zhou; Lihong Miao; Xuejuan Liu (Frontiers in Medicine)
IntroductionAcademic burnout is not uncommon and interferes with the role shift from nursing students to qualified nurses, aggravating a shortage of workforce in global healthcare system. However, there is currently a lack of research examining the relationship between family functioning, academic self-efficacy, and academic burnout in nursing students. The purpose of this study is to examine the relationship among family functioning, academic self-efficacy, and academic burnout among nursing students.Materials and methodsThis cross-sectional survey recruited 2,847 nursing students from a three-year vocational school located in Henan province in eastern China and used an online questionnaire to measure the participants’ basic information, family functioning, academic self-efficacy and academic burnout. Descriptive statistics, Pearson’s correlation, multiple linear regression and mediation analyses were used.ResultsThe mean (SD) score of academic burnout among nursing students was 53.98 (10.87). Family functioning (r = −0.39, p < 0.001) and academic self-efficacy (r = −0.64, p < 0.001) were negatively correlated with academic burnout. Family functioning (r = 0.46, p < 0.001) was positively correlated with academic self-efficacy. At the same time, academic self-efficacy plays a partial mediating role (indirect effect = −1.009; 95% CI, −1.114 to −0.910) in the influence of family functioning on academic burnout.ConclusionNursing students with higher level of family functioning may have a stronger sense of academic self-efficacy, which could lead to a lower level of academic burnout. This finding provides important guidance for educational administrators to formulate targeted strategies to prevent academic burnout of nursing students.